CYBER SECURITY IN THE DIGITAL AGE: CHALLENGES AND SOLUTIONS FOR PUBLIC ADMINISTRATION - Gunawan Widjaja (Adisam Publisher, 2025)
Cybersecurity in the digital age is a key challenge for public administrations, given the growth of increasingly sophisticated and destructive cyber threats. This demands effective strategies and solutions to protect critical infrastructure and sensitive data. A multi-layered technology approach, including system updates, encryption, and multi- factor authentication, combined with security training and policies for the workforce, is essential to respond to these threats. In addition, collaboration between governments, the private sector, and the international community should be optimised to strengthen responses to cyber threats. By implementing these measures, public administrations can significantly improve their digital security, ensure public services remain functional, and protect data from irresponsible exploitation.